Phenolic metabolism in Sarcandra glabra is mediated by distinct BAHD hydroxycinnamoyltransferases - Bömeke, Paul; Petersen, Maike (The Plant journal : for cell and molecular biology, 2025)
SUMMARY Sarcandra glabra (Chloranthaceae) has an elaborate phenolic metabolism, encompassing various hydroxycinnamic acid esters. This may imply that multiple hydroxycinnamoyltransferases are involved in establishing this spectrum of natural compounds. Five coding sequences from S. glabra, belonging to the superfamily of BAHD acyltransferases, have been amplified from S. glabra cDNA, and the proteins were expressed in Escherichia coli. By assaying the proteins biochemically, the main substrates of these enzymes were identified as p‐coumaroyl‐ and caffeoyl‐CoA as donor substrates together with varying acceptor substrates. SgHST mainly forms p‐coumaroyl‐ and caffeoylshikimic acid, but also the corresponding quinic acid esters as well as amides with 3‐ and 5‐hydroxyanthranilic acids. SgHQT1 predominantly catalyzes the formation of p‐coumaroyl‐ and caffeoyl‐5‐O‐quinic acid, while SgHQT2 correspondingly forms p‐coumaroyl‐ and caffeoyl‐4‐O‐quinic acid. To our knowledge, this is the first characterized enzyme forming cryptochlorogenic acid and its precursor p‐coumaroyl‐4‐O‐quinic acid. SgRAS synthesizes rosmarinic acid and its precursors (caffeoyl‐4′‐hydroxyphenyllactic, p‐coumaroyl‐4′‐hydroxyphenyllactic, p‐coumaroyl‐3′,4′‐dihydroxyphenyllactic acids) as well as amides with aromatic d‐amino acids. No substrates could be identified for the fifth sequence, SgHCT‐F, which phylogenetically groups with benzyl alcohol O‐benzoyltransferases. All enzymes, except SgHCT‐F, were fully kinetically characterized, and their expression in different tissues of S. glabra was assessed. Significance Statement Four genes and enzymes involved in the formation of hydroxycinnamoyl esters with shikimic, quinic, hydroxyphenyllactic, and benzoic acids as well as amides with hydroxyanthranilic and d‐amino acids were identified in Sarcandra glabra (Chloranthaceae), placed in a sister clade of the magnoliids. One enzyme catalyzes the direct formation of cryptochlorogenic acid, which has not been previously described.